2020
DOI: 10.3928/1081597x-20200826-02
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser–Assisted Allogenic Lenticule Implantation for Corneal Ectasia After LASIK: A 3-Year In Vivo Confocal Microscopic Investigation

Abstract: PURPOSE: To investigate morphological changes in the cornea and the implanted lenticule in patients with corneal ectasia after laser in situ keratomileusis (LASIK) and implantation using a lenticule from small incision lenticule extraction (SMILE). METHODS: Eight eyes of 8 patients with ectasia after LASIK from 2015 to 2018 at the Eye and ENT Hospital of Fudan Unversity were analyzed. For recipient eyes, lenticules were transferred with a mean cryoprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…The reimplantation of cryopreserved lenticules has been shown to be both safe and effective as a means of treating a range of ocular diseases, 11 , 12 and these preserved lenticules did not exhibit any apparent differences in subsequent wound healing when compared with fresh lenticules. 13 Glycerol is commonly used for prolonged preservation of human tissues and organs, including red blood cells, skin, and bone tissue. 14 16 Different glycerol-based cryopreservation solutions, however, exhibit distinctive properties.…”
mentioning
confidence: 99%
“…The reimplantation of cryopreserved lenticules has been shown to be both safe and effective as a means of treating a range of ocular diseases, 11 , 12 and these preserved lenticules did not exhibit any apparent differences in subsequent wound healing when compared with fresh lenticules. 13 Glycerol is commonly used for prolonged preservation of human tissues and organs, including red blood cells, skin, and bone tissue. 14 16 Different glycerol-based cryopreservation solutions, however, exhibit distinctive properties.…”
mentioning
confidence: 99%
“…The increasing popularity of this has made it easier to obtain SMILE-derived lenticules. The decellularized lenticule is a thin stromal layer with low immunogenicity and good biocompatibility, making it an excellent candidate for corneal stromal regeneration [21,22]. We have previously shown that decellularized lenticules could safely and effectively repair damage to the anterior cornea in rabbits [13].…”
Section: Discussionmentioning
confidence: 99%
“…Then, they included 7 similar patients treated with the same surgical method and followed up for three years, and all patients had satisfactory outcomes and no significant complications during the follow-up. 63…”
Section: Smile Lenticule In the Treatment Of Iatrogenic Keratectasiamentioning
confidence: 99%